Show that the sum from 1 to n of 1/(2n+1)(2n-1) is equal to n/(2n+1) by Induction

First we check that this is true for n=1: S1 = 1/(1x3)  which is equal to n/(2n+1) for n=1 therefore Sn = n/(2n+1) is true for n = 1. Next assume that it is true for n=k. Sk  = k/(2k+1). Now using this assumption we check that it is true for n=k+1: Sk+1 = Sk+ 1/(2(k+1) - 1)(2(k+1)+1). Rearranging this and substituting in k/(2k+1) for Sk we get Sk+1 = (k+1)/(2k+3) which is consistent with the original formula. Therefore we can say that since Sn = n/(2n+1) is true for n=1 and whenever it is true for n=k it is also true for n=k+1, it is true for all integer values of n larger than or equal to 1.

JF
Answered by Jamie F. Further Mathematics tutor

12998 Views

See similar Further Mathematics A Level tutors

Related Further Mathematics A Level answers

All answers ▸

How do I solve x^2 + x - 6 > 0 ?


By Differentiating from first principles, find the gradient of the curve f(x) = x^2 at the point where x = 2


Prove that ∑(1/(r^2 -1)) from r=2 to r=n is equal to (3n^2-n-2)/(4n(n+1)) for all natural numbers n>=2.


Give the general solution to (d2y/dx2) - 2dy/dx -3y = 2sinx


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences